Derivation of the σ‐w relationship for SFRC from prism bending tests. (March 2015) - Amin, Ali; Foster, Stephen J.; Muttoni, Aurelio
Abstract The material characterization of steel fibre‐reinforced concrete (SFRC), which is required for its implementation in design codes, should be based on nominal properties that describe its post‐cracking strength in tension. In the case of brittle and quasi‐brittle materials, such as concrete, the tensile parameters are often derived indirectly. However, for materials with more ductility, such as SFRC, there is conjecture as to whether or not an indirect measure may be used to establish the stress versus crack opening displacement relationship, such as the use of a three‐ or four‐point prism test combined with an inverse analysis. In this paper a simple and efficient inverse analysis technique is developed and shown to compare well with data obtained from direct tension tests. Furthermore, the methodology proposed by the fib Model Code for Concrete Structures 2010 has been investigated and recommendations made to improve its accuracy.